COMPARATIVE PROFILING OF PHYSICAL PERFORMANCE CHARACTERISTICS OF SINGLES AND DOUBLES BADMINTON PLAYERS - Singh, Pankaj; Bisht, Sujay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The nature and demands of singles and doubles game in badminton significantly differs, so does the physical performance of players of these categories. The motive of the present study was to present a comparative profile of physical performance characteristics of singles and doubles badminton players. Reaction time, flexibility, shoulder strength, leg explosive strength, grip strength, and thumb pinch were selected for assessment of physical performance. A total of 60 male players (30 from each category) were selected as subjects of age ranged between 18 to 25 years. Descriptive statistics and independent t-test were used as statistical tools to analyze the data. The results showed that there was a significant difference in reaction time, flexibility, grip strength, and thumb pinch of singles and doubles players; while no significant differences were observed for shoulder strength and leg explosive strength.